Tissue Culture On-chip Design using Multivariable Molecular Network - S. Authasing; S. Chantanetra; None S.Mitatha; P.P. Yupapin (My University, 2012)
This paper proposed tissue culture on-chip design using multivariable molecular network by using three network combinations such as star, bus and ring networks. A chip consists of star networks that allow the trapping molecule (nutrient or gene) circulation within design a circuit. In principle, the required nutrient can be trapped by the multivariable tweezers and transported to the required destinations. PANDA ring resonator is a modified add-drop filter can be generated and the molecules trapping transport is reviewed. In this work we are seeking for the optimizing results, which will be considered by choosing the suitable network parameters.
Keywords: Star (game theory); Star network; Microfluidic and Capillary Electrophoresis Applications